(3GdUjQaI GdGSdGejI aj GdLRGFQ (B:s (3OQGSI dehGUaGJ GdfehPL GdeUQaj GdGSdGej (B/s - (3YRhR, CMeOs; (3YdGe, YKeGfs ((3GdLRGFQ (B: s (3CdaG ddhKGFb ddfTQ hGdJhRjY (B, s, 2023)
(3jgJe HOQGSI CSGSjGJ GdfXGe GdeUQaj GdGSdGej, CSGdjH GdJehjd hGdGSJKeGQ aj GdeUGQa GdGSdGejI, fehPL GdQbGHI GdTQYjI Ydi GdeUGQa GdGSdGejI, YdGbI GdeUGQa GdeQcRjI HGdeUGQa GdGSdGejI , GdgjFGJ GdOGYeI ddYed GdeUQaj GdGSdGej, fTGW GdUjQaI GdGSdGejI aj GdLRGFQ(B.s
(3HjHdjhZQGajG(B: (3U U(B199-207s
Keywords: (3GdHfhcs; (3GdHfhc GdGSdGejIs